On phosphorus chemical shift anisotropy in metal (IV) phosphates and phosphonates: A 31P NMR experimental study. (20th October 2022) - Bakhmutov, Vladimir I.; Contreras‐Ramirez, Aida; Drake, Hannah; Zhou, Hong‐Cai
Abstract: The phosphorus chemical shift anisotropies, 31 PΔcs, and asymmetry parameters η were measured by the 31 P{ 1 H} NMR experiments in static and low‐frequency spinning samples of the zirconium phosphates and phosphonates and also in the mixed Zr (IV)/Sn (IV) phosphate/phosphonate material. The data obtained have shown a 111 connectivity in the HPO4 and PO3 groups, which does not change at modification and intercalation of the materials. The 31 PΔcs values of the phosphonate groups (43–49 ppm) significantly surpass the values characterizing the HPO4 groups (23–37 ppm). The 31 P Δcs values obtained for the metal (IV) phosphates were discussed in terms of P‐O distances. The 31 P chemical shift anisotropy parameters can help at elucidation of local structures in phosphate and phosphonate materials. Abstract : The 31 P chemical shift anisotropy parameters can help at elucidation of local structures in metal (IV) phosphate and phosphonate materials.